Screening for postpartum depression among postnatal mothers using Edinburgh postpartum depression scale - Shery Angel, Raja Kumar; Satyanarayan, Samyuktha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The postpartum period, marked by joy and various emotions, can also give rise to postpartum blues and, in severe cases, postpartum depression (PPD). Recognizing the importance of early detection, this study employed the Edinburgh postnatal depression scale (EPDS) to identify and raise awareness about PPD among postnatal women. Methods: A cross-sectional study at Chettinad Health Research Institute included 100 postnatal women. The EPDS questionnaire was used, and statistical analyses explored associations and predictors of PPD. Results: Demographic characteristics, EPDS scores, and prevalence of PPD were assessed. 50% exhibited EPDS scores ≥ 13, indicating PPD presence. No significant associations were found between age, delivery method, or gestational age and EPDS scores, but pre-existing medical conditions were linked to higher scores. Conclusions: This study provides insights into the multifaceted nature of PPD, emphasizing the need for tailored interventions and ongoing research to support postnatal women. The prevalence observed underscores the urgency for awareness and timely interventions to alleviate the burden of PPD on mothers and families.